Exploring the impact of covid-19 lockdown on access to library resources by University of Zambia students: a case of the school of Samora Machel Veterinary Medicine - Tembo, Sarah Gwayi; Chewe, Pailet (Journal of Social Review and Development, 2022)
Objectives- The main objective of this study was to examine the impact of the 2020/21 COVID-19 pandemic lockdown on access to information resources and services by Veterinary Medicine students at the University of Zambia. Methods- The research adopted a survey design approach in which a semi-structured questionnaire was employed for data collection. A convenient sampling technique was used to recruit fifty (50) participants. Data was analysed using Statistical Package for the Social Sciences version 20. Results- This work has found that 54% of the respondents were ignorant of the information resources and services that were available via remote access during the pandemic lockdown while 46% were aware. The study has further established that 46% of the respondents accessed the resources while 54% did not. Further findings reveal that past examination papers were the most accessed resources. The major challenges encountered include unreliable Internet connectivity and stringent login credentials. Conclusions- The study concludes that COVID-19 pandemic lockdown negatively affected students’ access to information resources and this ultimately influenced their academic performance. It is recommended that the library realign its services with the changing library and information landscape. These findings provide useful information on how librarians can remodel their services to match new demands presented by the COVID-19 pandemic.